Buddhist Education Philosophy in the 21st Century - วิภาตะศิลปิน เนตรชนก (Journal of Educational Review Faculty of Education in MCU, 2018)
The world is changing there are fields of knowledge called occur all the time. Many fields of knowledge are treated as out-of-date and they are replaced by the modern ones. Through technology, the knowledge can be transferred rapidly and borderlessly. The duty of human is not only learning from others or documents but also seeking the knowledge themselves. To know how to use the tool, method, process, idea, analysis and synthesis in knowledge can help develop human knowledge in perfect. The effective process in searching and accessing knowledge is through ‘Buddhist education philosophy’. With this process, human beings can not only search and access the knowledge but also lead to lifelong learning in the scope of education in the 21st century.